HEMATOLOGY PROFILES AND DISEASE SEVERITY OF PEDIATRIC DENGUE VIRUS INFECTION AT A TERTIARY HOSPITAL IN SURABAYA, INDONESIA - Annisa Fira Salsabila; Juniastuti; Dominicus Husada; Dwiyanti Puspitasari (Majalah Biomorfologi, 2024)
Highlights Dengue virus infections exhibit a spectrum of clinical manifestations, ranging from asymptomatic cases to severe disease, with the potential for fatalities if not managed effectively. Hematology factors significantly contribute to the severity of dengue virus infection.   Abstract Background: The escalating incidence of dengue cases in Surabaya, Indonesia, underscores the imperative to comprehend the hematology profiles and disease severity in pediatric patients affected by dengue virus infections (DVI). As the prevalence of DVI continues to surge, understanding the nuanced clinical manifestations becomes paramount for effective management and mitigation of the disease burden. Objective: This study aimed to characterize the hematology profiles and the disease severity of dengue virus infections (DVI) among pediatric patients hospitalized at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia throughout 2019. Material and Method: A retrospective descriptive cross-sectional study was conducted using secondary data from medical records. Pediatric patients aged six months to 18 years were enrolled. A total sampling method comprised 67 patients meeting the inclusion criteria. Result: Severe thrombocytopenia was most commonly observed in dengue hemorrhagic fever (DHF) III cases (36.4%), while leukopenia was predominant in DF cases (42.2%). High hematocrit levels were more prevalent in DHF III cases (27.3%), and high hemoglobin levels were most frequently identified in DHF II and DHF III cases (33% in each case). Significant differences in DVI severity were observed in platelets and hemoglobin levels (p=0.0002 and p=0.0066, respectively) but not in leukocyte and hematocrit levels. Conclusion: Mild thrombocytopenia was prevalent in Dengue Fever (DF), while severe thrombocytopenia was most prevalent in Dengue Hemorrhagic Fever (DHF) grade III. Leukopenia was prominent in DF patients, and platelets and hemoglobin levels varied across severity of DVI. These findings provide insights for improved clinical management and diagnostic criteria refinement.